The Role of Procurement and Supply of Agricultural Products in the Market Economy of the Country - Orujova Adjar Azhdar kyzy (Research Parks Publishers, 2021)
Ensuring food security of the state is one of the most important issues in modern conditions. Effective state regulation of the agricultural sector, which is considered one of the most important and priority sectors of the economy, is considered one of the market relations in modern times, as in different periods. The agricultural sector is also the basis of food security. Preventive measures taken by the state envisage the establishment of food independence in the Republic of Azerbaijan. The